The Development of TOEFL ITP Learning Determination Application Using Forward Chaining Method - Nurrahmi, Herly; Amalia Putri, Liza (Devotion : Journal of Research and Community Service, 2024)
Adequate English language competency is very necessary in today's modern era so as not to discuss difficulties in global communication and interaction. The average English language skills of students or generations aged 18-20 years in Indonesia show low results. To solve this problem, efforts are needed to increase English language competency through appropriate learning activities. The system development method for this application uses the waterfall method. The use of the forward channeling method in an expert system will help determine appropriate and effective ways of teaching and learning English to students. The aim of this research is to apply an expert system to obtain recommendations for effective English learning based on TOEFL ITP scores. Three aspects of TOEFL ITP, namely listening, reading and structure, will be used in the analysis process using forward chaining. The forward chaining method carries out processing starting from the data set and then performs inference according to the rules used until the optimal inference is found. The inference engine will continue to go through the process to arrive at the right decision result. The expert system application is designed to be website-based so that it makes it easier for users to use it at any time